Resistance to Carbapenems among Enterobacteriacae, Pseudomonas Aereuginosa and Acinetobacter Baumannii segregated from Patients at Tertiary Care Hospitals of Peshawar - Salam, Abdul; Muhammad, Asim; Khan, Aurangzeb (ADVANCES IN BASIC MEDICAL SCIENCES, 2022)
Objective: The objective of this study is to ascertain the incidence of Carbapenem resistant Enterobacteriaceae and to evaluate the pattern of antibiotics resistance for treatment of infections caused by these bacteria. Methodology: This retrospective study was done in Microbiology department, Abasyn University Peshawar and Department of Microbiology, OK Quality Lab and Research Centre Peshawar, Pakistan. Data of 300 samples were studied from Medical Microbiology records of three tertiary care hospitals of Peshawar from November, 2020 to March, 2021.Microbial confirmation was done using API system of identification and antimicrobial resistance was determined by modified Kirby-bauer method. Detection of carbapenamase enzyme was done through Modified hodge test in this study. Results: A total of 300 samples were studied. Those with a positive cultures, 71(49.3%) were males and 73(50.7%) were females. Out of these, 51(35.4%) cases were of UTI with positive urine culture and 39(27.1%) were diagnosed through pus culture. E.Coli was commonest microbe found while carbapenems had significant antibacterial activity. Modified Hodge test reveals that out of (n=46) only 8(17.4%) manifested phenotypic gene expression. Conclusion: Our study identifies the emergence of Carbapenem resistant Enterobacteriaceae, P.aeruginosa and A.baumannii in local population. This situation is alarming, due to loss of options for the physicians in treating such multi-drug resistant infections. It is imperative to formulate a startegy for antimicrobial stewardship and control antimicrobial resistance in our country. Key words: Antibiotic resistance, Carbapenems, Modified hodge test